Improving School Transition and Performance: Democratization of Secondary Education in St. Kitts and Nevis - Halliday, Joseph Jacob (UNICEF CAO, 1997)
This paper addresses a select number of the critical issues that confronted the political and educational administrators in St. Kitts and Nevis during the development and implementation of a macro-educational innovation in the 1960s and 1970s, viz. the democratization of secondary education.
Keywords: Educational innovations